Creencias religiosas y su influencia en la sexualidad de una pareja - Escobar Aguirre, Jairon Fernando (2020)
In the present case study, the theme of religious beliefs and the influence on the sexuality of a couple with believing indoctrination was addressed, the data necessary for the elaboration of this study was collected through interviews and psychometric instruments such as the Spanier dyadic adjustment scale and the Golombok-Rust inventory of sexual satisfaction, that was carried out on a newly married couple and the results obtained were low sexual satisfaction on both sides. Some suggestions were made for the couple, thus giving family psychoeducation and some tips that will be necessary to strengthen the marriage and the sexual bond, so that the satisfaction of the couple will be improved.